Drivers of Mobile Game Addiction and Its Impact on Game Loyalty and In-App Purchase Intention Among Gen-Z in Indonesia - Miftah Mahardhika Airlangga; Lizar Alfansi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to analyze the influence of flow experience, escapism, and playfulness on mobile game addiction, and to examine how mobile game addiction affects game loyalty and in-app purchase intention among Generation Z in Indonesia.Method: A quantitative research design was employed. Data were collected through an online questionnaire distributed to 210 respondents. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software.Result: The results show that flow experience and escapism significantly and positively influence game addiction. In contrast, playfulness has a significant negative effect, suggesting that enjoyment alone does not necessarily lead to addictive behavior. Game addiction positively influences both game Loyalty and in-app purchase intention. However, game loyalty does not have a significant effect on in-app purchase intention.Practical Implications for Economic Growth and Development: These findings offer valuable insights for mobile game developers seeking to enhance user engagement and revenue. By leveraging flow experience and escapism, developers can increase both addiction tendencies and in-app spending. This approach contributes to the growth of Indonesia’s digital economy through strategic monetization.Originality/Value: This study adds to the limited body of research examining psychological drivers of game addiction and their economic implications within the context of Generation Z in a developing digital market.